Using Epi Map graphic data presentation software for regional targeting - Slack, Alison T.; Morris, Saul Sutkover (International Food Policy Research Institute, 1999)
Epi Map, a powerful new mapping software program, is now available to the public from the Centers for Disease Control (CDC) in collaboration with the World Health Organization (WHO). The program can be used to identify spatial variation in household food security and nutrition-relevant variables, such as population densities, crop yields, and malnutrition rates. Geographic clustering and trends are clearly identified, and the maps can provide a means of targeting vulnerable populations, such as those with high rates of poverty or high levels of food insecurity.